(untitled) (Journal of the College of Basic Education, 2026)
The field of idiomacity is considered as an interesting concept, particularly when it comes to second language (L2) acquisition and English Foreign Language learners (EFL). The ability of utilizing and mastering idioms whether in speaking or writing is regarded as indicator towards proficiency. This study is conducted to investigate the challenges that encountered by Baghdad university students in learning English idioms, and the strategies that can be employed for the sake of understanding idiomatic expressions. The subjects were 60 fourth-year English major students from Baghdad university who enrolled in the first semester of academic year 2025/2026. A survey questionnaire on a five-point Likert scale adapted from (Orfan, 2020b) was used to collect the data from the participants. The findings showed that Baghdad university students had a positive attitude towards the importance of learning idioms and their critical role in effective English communication with overall mean score of (3.98), particularly, 45% of respondents agreed and 30% strongly agreed, it is important to encourage EFL students to learn idioms for effective communication. In contrast, just 3% disagreed, 2% strongly disagreed, and 20% were neutral. The findings also revealed that the participants had considerable difficulty in learning and understanding idioms with an overall mean difficulty score of (3.22). For instance, 38.3% of the participants agreed and 3.3% strongly agreed (41.6% total agreement), that idioms are difficult because they are not well taught in English classes, while 23.3% disagreed or strongly disagreed. A considerable proportion (35%) selected the neutral option. In terms of strategies, the study revealed that the most commonly used strategies were learning idioms outside of the classroom with (57%) agreeing or strongly agreeing, and a few disagreeing (15%), inserting them into sentences with (55%) agreeing or strongly agreeing, and (12%) disagreeing, guessing the meaning of idiomatic expressions from context with (48%) agreeing or strongly agreeing, and (19%) disagreeing, and by translating them to the first language with (55%) agreeing or strongly agreeing, and (22%) disagreeing. The researcher suggested the greater focus that should be made on explicit instruction of idioms within the classroom, through the integration of contextualized practice and communicative activities in order to enhance the learners’ idiomatic competence.